The Most Dangerous Man in Detroit: Walter Reuther and the Fate of American Labor - Turrini, Joseph M. (Labour / Le Travail, 1998)
The article reviews the book, "The Most Dangerous Man in Detroit: Walter Reuther and the Fate of American Labor," by Nelson Lichtenstein.